Cross sectional, comparative study of serum erythropoietin, transferrin receptor, ferritin levels and other hematological indices in normal pregnancies and iron deficiency anemia during pregnancy. (August 2016) - Sharma, Jai B.; Bumma, Sirisha D.; Saxena, Renu; Kumar, Sunesh; Roy, Kallol K.; Singh, Neeta; Vanamail, P.
Abstract: Objective: To test the correlation of the serum erythropoietin levels, serum transferrrin receptor levels and serum ferritin levels along with other hematological parameters in normal pregnant and anemic pregnant patients. Study Design: In a prospective study, 120 pregnant women were recruited between 18 and 36 weeks of gestation; 53 normal pregnant patients, 67 anemic pregnant patients, in which, 17 had mild, 30 had moderate anemia, 20 had severe anemia. A blood sample was taken. The various hematological parameters, hemoglobin (Hb), mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC), total iron binding capacity (TIBC), serum ferritin, percentage saturation of iron, serum erythropoietin (SEPO) levels, serum transferrin receptors (STfRS) were performed. For statistics, Student's ' t ' test, Pearson's Chi test, Mann Whitney test and Bartlett test were used as per data. Results and Conclusion: MCV was significantly reduced in anemic pregnancies as compared to non-anemic pregnancies (80.2 ± 9.6 vs 94.12 ± 9.8 fl, p = 0.001), MCHC was also reduced in them (30.2 ± 3.38% vs 34.2 ± 2.33%, p = 0.176), TIBC was significantly increased in anemic pregnancies (343.31 ± 28.54% vs 322.88 ± 23.84%, p = 0.001), serum ferritin was significantly reduced (24.9 ± 10.48 μg/L vs 31.03 ± 9.98 μg/L, p = 0.001), percentage saturation of iron was also reduced (53.85 ± 13.21% vs 62.04 ± 15.79%, p = 0.0024), serum erythropoietin levels were significantly higher in anemic women (26.24 ± 26.61 mU/ml vs 18.12 ± 19.08 mU/ml, p = 0.064). The levels were significantly higher in severe anemia (46.5 ± 46.8 mU/ml than in moderate anemia 27.4 ± 28.1 mU/ml and mild anemia 22.8 ± 22.8 mU/ml. Serum transferrin receptors were significantly higher in anemic pregnancies than in non-anemic pregnancies (1.40 ± 0.0802 μg/ml vs 1.08 ± 0.641 μg/ml, p = 0.019) with rise being higher in severe anemia (2.28 ± 0.986 μg/ml) than in moderate (1.4 ± 0.816 μg/ml) and mild anemia (1.16 ± 0.702 μg/ml). Conclusion: Various hematological parameters especially sTfR, serum erythropoietin, serum ferritin and sTfR/log ferritin levels correlate with the severity of anemia.